Effects of moderate shade and irrigation with eutrophicated water on the nitrogen economy of Mediterranean oak seedlings (Flora - Morphology, Distribution, Functional Ecology of Plants, 2008)
We evaluated the effects of moderate shade (43% vs. 100% of full sunlight) and irrigation with eutrophicated river water (daily vs. alternate-day watering) on growth and nitrogen economy of seedlings of three Mediterranean oak species, two evergreen (Quercus coccifera, Quercus ilex subsp. ballota) and a deciduous (Quercus faginea), grown in pots outdoors. Seedling biomass, N pool, N concentration and N losses by litter fall were measured at the beginning (March 2002) and end (November 2002) of a growing season. All species showed an increase of biomass and N pool under shade and/or high irrigation, while only Q. coccifera – from more arid regions – did the same under full sunlight and low irrigation. At the end of the experiment, biomass of the evergreens was higher in shade than in sun, and in high than in low irrigation, while Q. faginea – from more humid zones – responded to irrigation only. Shade-induced growth was accompanied by a decline in N concentration in the evergreens, but irrigation reduced N concentration only of Q. faginea. Shade, but not irrigation, reduced above-ground N loss. We conclude that both treatments differentially affected the evergreen and the deciduous oaks, probably due to differences in plant hydraulic and stomatal conductance. Although both treatments have similar effects on the growth of evergreens, they produced different effects on seedling N economy, which may have important consequences on future ﬁeld seedling performance

Effects of moderate shade and irrigation with eutrophicated water on the nitrogen economy of Mediterranean oak seedlings - Castro-Díez, Pilar; Navarro, Javier; Maestro, Melchor (Flora - Morphology, Distribution, Functional Ecology of Plants, 2008)
We evaluated the effects of moderate shade (43% vs. 100% of full sunlight) and irrigation with eutrophicated river water (daily vs. alternate-day watering) on growth and nitrogen economy of seedlings of three Mediterranean oak species, two evergreen (Quercus coccifera, Quercus ilex subsp. ballota) and a deciduous (Quercus faginea), grown in pots outdoors. Seedling biomass, N pool, N concentration and N losses by litter fall were measured at the beginning (March 2002) and end (November 2002) of a growing season. All species showed an increase of biomass and N pool under shade and/or high irrigation, while only Q. coccifera – from more arid regions – did the same under full sunlight and low irrigation. At the end of the experiment, biomass of the evergreens was higher in shade than in sun, and in high than in low irrigation, while Q. faginea – from more humid zones – responded to irrigation only. Shade-induced growth was accompanied by a decline in N concentration in the evergreens, but irrigation reduced N concentration only of Q. faginea. Shade, but not irrigation, reduced above-ground N loss. We conclude that both treatments differentially affected the evergreen and the deciduous oaks, probably due to differences in plant hydraulic and stomatal conductance. Although both treatments have similar effects on the growth of evergreens, they produced different effects on seedling N economy, which may have important consequences on future ﬁeld seedling performance
Keywords: deciduous tree; Drought stress; evergreen tree; leaf shedding; Quercus; seedling growth

Seasonal variability of dry matter content and its relationship with shoot growth and nonstructural carbohydrates - Palacio, Sara; Milla, Rubén; Albuixech, Jorge; Pérez-Rontomé, Carmen; Camarero, Jesús Julio; Maestro, Melchor; Montserrat-Martí, Gabriel (New Phytologist, 2008)
* • This study assesses how different phases of shoot growth underlie seasonal change in leaf and stem dry matter content (LDMC and SDMC, respectively) of 12 woody Mediterranean species. The relationship between LDMC and nonstructural carbohydrate (NSC) concentrations is also explored and the seasonal vs interspecies variability of LDMC compared. * • LDMC, SDMC and shoot elongation rate (SER) were measured on a monthly basis for a minimum of 12 months. Bud growth rate (BGR) and NSC concentrations were also assessed in several of the study species. * • LDMC and SDMC decreased during shoot elongation in spring and increased in summer, showing a significant negative correlation with SER, but were unrelated to BGR. Half of the species analysed showed a positive relationship between LDMC and NSC. Seasonal fluctuations of LDMC within species were higher than interspecies differences, and species ranking was significantly affected by the month of sampling, except during winter months. * • Seasonal changes in LDMC and SDMC are mainly related to shoot elongation phenology, and NSC sink–source relationships between old and growing organs can explain this relationship in some species. Owing to the high seasonal variability in LDMC, it is recommended that samples for comparative purposes should be collected as close to the winter as possible.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 18643937
Keywords: Carbohydrate Metabolism; functional classifications; leaf dry matter content (LDMC); leaf traits; leaf water status; Mediterranean; Phenology; Plant Development; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: metabolism; Plant Shoots; Plant Shoots: growth & development; Plant Shoots: metabolism; Plant Stems; Plant Stems: growth & development; Plant Stems: metabolism; Plants; Plants: metabolism; Seasons; shoot growth; Species Specificity

Seasonal variability of dry matter content and its relationship with shoot growth and nonstructural carbohydrates (New Phytologist, 2008)
* • This study assesses how different phases of shoot growth underlie seasonal change in leaf and stem dry matter content (LDMC and SDMC, respectively) of 12 woody Mediterranean species. The relationship between LDMC and nonstructural carbohydrate (NSC) concentrations is also explored and the seasonal vs interspecies variability of LDMC compared. * • LDMC, SDMC and shoot elongation rate (SER) were measured on a monthly basis for a minimum of 12 months. Bud growth rate (BGR) and NSC concentrations were also assessed in several of the study species. * • LDMC and SDMC decreased during shoot elongation in spring and increased in summer, showing a significant negative correlation with SER, but were unrelated to BGR. Half of the species analysed showed a positive relationship between LDMC and NSC. Seasonal fluctuations of LDMC within species were higher than interspecies differences, and species ranking was significantly affected by the month of sampling, except during winter months. * • Seasonal changes in LDMC and SDMC are mainly related to shoot elongation phenology, and NSC sink–source relationships between old and growing organs can explain this relationship in some species. Owing to the high seasonal variability in LDMC, it is recommended that samples for comparative purposes should be collected as close to the winter as possible.

Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species (Tree Physiology, 2006)
Shade and irrigation are frequently used to increase the success of Mediterranean Quercus spp. plantations. However, there is controversy about the combined effects of these treatments on plant performance. We assessed the effects of two irradiances (full sunlight and moderate shade) and two summer watering regimes (high (daily) and low (alternate days)) on leaf and whole-plant traits of 1-year-old seedlings of Quercus coccifera, Q. ilex subsp. ballota and Q. faginea grown outdoors for 8.5 months. Leaf traits included measures of morphology, nitrogen concentration, gas exchange and photochemical efficiency, and measures of whole-plant traits included biomass allocation patterns, growth phenology, across-summer leaf area change and relative growth rate (RGR).Moderate shade reduced leaf mass per area, increased photochemical efficiency, maximum carbon assimilation rate (Amax) and allocation to leaves, and prolonged the growing period in one or more of the species. Daily watering in summer increased Amax of Q. ilex and prolonged the growing period of Q. ilex and Q. faginea. Both treatments tended to increase RGR. The effect of shade was greater in the low-watering regime than in the high-watering regime for two of the 15 studied traits, with treatment effects being independent for the remaining 13 traits. Leaf nitrogen and the ability to maintain leaf area after the arid period, rather than biomass allocation traits, explained the variation in seedling RGR. Trait responsiveness to the treatments was low and similar among species and between study scales, being unexpectedly low in Q. faginea leaves. This may be because selective pressures on leaf plasticity act differently in deciduous and evergreen species. We conclude that moderate shade and daily summer watering enhance the performance of Mediterranean Quercus seedlings through species-specific mechanisms.
From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)

Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G.; Maestro, Melchor (Tree Physiology, 2006)
Shade and irrigation are frequently used to increase the success of Mediterranean Quercus spp. plantations. However, there is controversy about the combined effects of these treatments on plant performance. We assessed the effects of two irradiances (full sunlight and moderate shade) and two summer watering regimes (high (daily) and low (alternate days)) on leaf and whole-plant traits of 1-year-old seedlings of Quercus coccifera, Q. ilex subsp. ballota and Q. faginea grown outdoors for 8.5 months. Leaf traits included measures of morphology, nitrogen concentration, gas exchange and photochemical efficiency, and measures of whole-plant traits included biomass allocation patterns, growth phenology, across-summer leaf area change and relative growth rate (RGR).Moderate shade reduced leaf mass per area, increased photochemical efficiency, maximum carbon assimilation rate (Amax) and allocation to leaves, and prolonged the growing period in one or more of the species. Daily watering in summer increased Amax of Q. ilex and prolonged the growing period of Q. ilex and Q. faginea. Both treatments tended to increase RGR. The effect of shade was greater in the low-watering regime than in the high-watering regime for two of the 15 studied traits, with treatment effects being independent for the remaining 13 traits. Leaf nitrogen and the ability to maintain leaf area after the arid period, rather than biomass allocation traits, explained the variation in seedling RGR. Trait responsiveness to the treatments was low and similar among species and between study scales, being unexpectedly low in Q. faginea leaves. This may be because selective pressures on leaf plasticity act differently in deciduous and evergreen species. We conclude that moderate shade and daily summer watering enhance the performance of Mediterranean Quercus seedlings through species-specific mechanisms.
From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)The following values have no corresponding Zotero field: accession-num: 16356909
Keywords: Agriculture; Agriculture: methods; Analysis of Variance; biomass allocation; carbon assimilation rate; fluorescence; Mediterranean Region; Phenology; Phenotype; Plant Leaves; Plant Leaves: growth & development; Plant Shoots; Plant Shoots: physiology; Quercus; Quercus: drug effects; Quercus: growth & development; Quercus: physiology; Relative growth rate; Seedling; Seedling: drug effects; Seedling: physiology; water; Water: metabolism; Water: pharmacology